ANALISIS IMPLEMENTASI PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL SESUAI DENGAN PERATURAN PEMERINTAH ( PP ) 71 TAHUN 2010 ( Study pada Pemerintah Daerah Kabupaten Karimun ) - ', Supriyono; ', Desmiyawati; Azlina, Nur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The formulation of the research problem is as follows: 1). How readiness district government that Karimun indicated by the commitment, human resources, infrastructure and information systems in mengimplementa sikan PP 71 Year 2010 About the Government Accounting Standards (SAP) Based Accrual?, What are the obstacles in the implementation of Regulation No. 71 Year 2010, on Accounting Standards Government (SAP)? 2). What is an obstacle in the implementation of Regulation No. 71 Year 2010, concerning the Government Accounting Standards (SAP)? 3). How acceleration strategy implementation models PP 71 Year 2010 concerning Governmental Accounting Standards (SAP)? 3). How is the acceleration of the implementation of strategic models PP 71 Year 2010 concerning Governmental Accounting Standards (SAP), the results of this research show that commitmet has significant 0,388,the analysis with the human resource variable in has significant 0,369 , infrastructure variable in has significant 0,352 and information system it show positif significant 0,354. Of the research in the know that the implementation of the application of accrual-based government accounting standards in Karimun regency government is ready to implement the category of Government Accounting Standards (SAP) based acrual accordance with Government Regulation (PP) 71 in 2010.Keywords : implementation, accounting, accrual basis, government regulations